What are The major Problems Faced By Farmers In East Africa? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Mainza Mugoya from Eastern Africa Farmers' Union. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya